ANALISIS PEMILIHAN SUPPLIER CARTON BOX DI PT XYZ - Harahap, Ummi Kalsum; Sirait, Ganda (LPPM Universitas Putera Batam, 2021)
Supplier selection is one of the most important decision making problems. In the manufacturing industri, one of the company’s important activities to maintain the continuity of the production process is activity of purchasing raw materials by suppliers. This research was conducted in Submaterial Department of PT XYZ. The company focuses on the manufacture of plastic garbage bags and food storage bags. The method used in this study is the AHP and TOPSIS method. The result showed that there are 5 criteria with 13 subcriteria. Quality (0.3497) criterion is the most important criterion in supplier selection, the sub-criteria that has the most important is the suitability of price with the quality of the product produced (0.2150) and PT IIB has a weight of the largest is (0.2017). Based on the preference value, PT IIB has the largest preference value, which is (0.9187). This shows that PT IIB is in the most important order so that it becomes the best prioritized supplier in fulfilling the supply of carton boxes to PT XYZ.